2014
DOI: 10.1186/ar4671
|View full text |Cite
|
Sign up to set email alerts
|

Clinical course after corticosteroid therapy in IgG4-related aortitis/periaortitis and periarteritis: a retrospective multicenter study

Abstract: IntroductionImmunoglobulin G4 (IgG4)–related aortitis/periaortitis and periarteritis are vascular manifestations of IgG4-related disease. In this disease, the affected aneurysmal lesion has been suspected to be at risk of rupture. In this study, we aimed to clarify the clinical course after corticosteroid therapy in IgG4-related aortitis/periaortitis and periarteritis.MethodsWe retrospectively evaluated clinical features, including laboratory data, imaging findings and the course after corticosteroid therapy, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
78
3
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(90 citation statements)
references
References 37 publications
(41 reference statements)
7
78
3
2
Order By: Relevance
“…3 Meanwhile, IgG4-related periaortitis has been considered to pose little risk of aortic rupture because of the lack of aortic dilatation. 9 However, a recent report described a case of a false aneurysm developing from IgG4-related periaortitis caused by corticosteroid therapy, just as that observed in our present case. 10 In both cases, endovascular repair was a successful initial treatment for the false aneurysm.…”
Section: Discussionsupporting
confidence: 43%
“…3 Meanwhile, IgG4-related periaortitis has been considered to pose little risk of aortic rupture because of the lack of aortic dilatation. 9 However, a recent report described a case of a false aneurysm developing from IgG4-related periaortitis caused by corticosteroid therapy, just as that observed in our present case. 10 In both cases, endovascular repair was a successful initial treatment for the false aneurysm.…”
Section: Discussionsupporting
confidence: 43%
“…An observational study in IgG4-positive periaortitis showed a signifi cant reduction of infl ammatory parameters and vessel wall enlargement under variable prednisolone treatments, initiated with 15 -50 mg/d and tapered to 5 -10 mg/d during 6 -12 months. Aortic wall diameter decreased by 50 % within the fi rst two months of treatment; after that a further decrease was observed in half of the patients [73]. There were a few patients with IAA in whom aneurysmatic dilation increased despite reduction of the adventitial infl ammatory border.…”
Section: Infl Ammatory Abdominal Aneurysm (Iaa)mentioning
confidence: 96%
“…Mizushima and colleagues highlighted three aspects relating to corticosteroid therapy and clinical course in IgG4-related vascular diseases: 1) the possibility of latent existence and progression, 2) the efficacy of corticosteroid therapy in preventing new aneurysm formation in patients without luminal dilatation, and 3) the possibility that a small proportion of patients may actually develop luminal dilatation. 50) The therapeutic corticosteroid dosage required to treat IgG4-related diseases differs case-by-case, and Tajima and colleagues have suggested that treatment of IgG4-related cardiovascular diseases might require higher doses of corticosteroids than other IgG4-related diseases. 51) IgG4-related diseases can involve any organs.…”
Section: Discussionmentioning
confidence: 99%